“Sacherklärungen” in biblischen texten - vorkommen und bedeutung für die Bibelübersetzung - C. Stenschke (Acta Theologica)
In several places in the Old and New Testament narratives we find different explanatory notes. Through them, the biblical authors provide the necessary background information so that the readers can better understand the actions or words of the protagonists or geographical locations. On the one hand these notes indicate that at least some of the intended readers were not familiar with all aspects of the environment of the biblical events. Therefore such notes allow some indirect conclusions concerning the readers. On the other hand these notes show the intention of the biblical authors to communicate effectively. They wanted to communicate in detail with their readers and in order to do so they “brought” the world of the narrated events to the readers. Their texts should be understood without further information. These explanatory notes carry several implications for present day Bible translation and the content of modern Bible editions. These notes also indicate that that the biblical authors did not universalise their message for the sake of easier communication. Rather they left their message in its geographical, historical and cultural context and added the necessary information so that it nevertheless could be understood. This underlines God’s revelation to concrete people in history.